Assessment of the Photo-catalytic Efficiency of Palladium/Silver Doped TiO2 Nanoparticles Using X-ray Diffraction and Brunauer-Emmet-Teller Analysis - UGWOKE, AO; OMONIYI, KI (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
Research on Titanium dioxide (TiO2) has attracted extensive interest because of its potential applications to photocatalysis, chemical sensors, solar cell electrodes and hydrogen storage materials. This study investigates the effect of Palladium (Pd) and Silver (Ag) doping on the photocatalytic efficiency of TiO2 nanoparticles. The effect of modified TiO2 with palladium, silver and co-dopant of palladium and silver on TiO2 with its photocatalytic efficiency was studied using X-ray diffraction (XRD) and Brunauer–Emmet–Teller (BET). The photo-catalysts were prepared by the sol immobilisation method and characterised using XRD and BET techniques. The textural properties, such as surface area and pore size distribution of Ag/TiO2, Pd/TiO2 and Ag/Pd-TiO2 were analysed by using N2 physisorption using a NOVA 2200e. The X-ray diffraction patterns of the dopants were found to be uniform with the standard P25 Degussa TiO2. From the peak formation of anatase and rutile phases, it was found that the Pd/TiO2 formed a uniform matrix of anatase and rutile, indicating that palladium ion disperses evenly on P25 Degussa TiO2. The peak formation on Ag/TiO2 and Pd/AgTiO2 shows the same uniform distribution of silver and palladium ions, only that foreign peaks were observed on the formation of anatase and rutile because of impurity in silver. The crystalline size of the catalyst and full width at half maximum (FWHM) were also calculated at different angles of diffraction. The BET shows that the photocatalysts were mesoporous and had a type IV isotherm. The high mesopore of the catalyst increases its photocatalytic activity, and also type IV isotherm. The BET analysis shows that the pore size distribution of the catalyst is between 2nm and 50nm, which shows that the catalyst is mesoporous. It also gives a high surface area with high volume and low pore size (crystalline size), which increases the photocatalytic efficiency. The study concluded that the doping and codoping of palladium and silver on TiO2 improve the photocatalytic activity of P25 degusa TiO2 by producing more active phase (anatase), which favours photocatalysis. So, co-doping of palladium and silver on TiO2 can serve as a strategy for the design of high-performance photocalysts for environmental benefits. These results demonstrate the potential of Pd/Ag co-doped TiO2 for advanced environmental remediation applications.